A Comparative Investigation on Adsorption Performances of Activated Carbon Prepared from Coconut Husk Fiber and Commercial Activated Carbon for Acid Red 27 Dye - A. Al-Aoh, Hatem; Jamil Maah, M.; Yahya, Rosiyah; Radzi Bin Abas, M. (Asian Journal of Chemistry, 2013)
The adsorption of acid red 27 dye on activated carbon fiber and granular activated carbon were studied in a batch system. The effects of initial concentration, agitation time, solution pH and temperature were examined. Adsorption isotherms were described using both the Langmuir and Freundlich models at three different temperatures. It was found that, the Langmuir model fits well with the experimental data at each temperature. The pseudo-first-order, pseudo-second-order and intra-particle diffusion models were used to examine the kinetics data. The results obtained showed that the empirical kinetics data of activated carbon fiber at 60 and 100 mg/L were well described only by the pseudo-second-order model. The intraparticle diffusion was involved at 200 mg/L for activated carbon fiber and at each tested concentration for granular activated carbon. It was observed that activated carbon fiber has a higher adsorption capacity and adsorption rate than that of granular activated carbon. Adsorption thermodynamic parameters were estimated and the values of DHº, DSº and DGº obtained indicate that the adsorption of acid red 27 on activated carbon fiber and granular activated carbon were exothermic and spontaneous processes.